Pola Pelayanan Penelusuran Informasi Untuk Memenuhi Kepuasan Pemustaka Di Perpustakaan Proklamator Bung Hatta Bukittinggi - Salsabila, Syifa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this thesis is the lack of responsive service and the difficulty of finding collections or information and what is needed at the Hatta Bukittinggi Proclamator Library, both digital search (OPAC) and conventional (direct search to the shelf). The purpose of this study is to find out the form of information retrieval service patterns to meet user satisfaction and find out the obstacles and efforts in information retrieval services. The type of research used by the researcher is descriptive research with a qualitative approach. The data collection techniques used by the researcher are observation, interviews, and documentation. The data analysis techniques used by the researcher are data reduction, data presentation, conclusion drawing and verification. The assurance of data validity in this study uses triangulation of sources, techniques and time. The form of information retrieval at the Hatta Bukittinggi Proclamation Library is digital search (OPAC) and conventional (direct search to the shelf). The obstacles and efforts of information retrieval services to meet the satisfaction of users at the Hatta Bukittinggi Proclamation Library are users who cannot find the collections or information they need on the shelves. The effort is that the library must provide direction or guidance so that users in searching for information find the collections they need. For other obstacles such as library networks, the library has provided PTI services that repair damaged servers and problematic networks at the Hatta Proclamator Library so that the work carried out can run more effectively and efficiently.